(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article examines the comparative linguistic characteristics of information technology terms in the British National Corpus and the Uzbek National Corpus. The study focuses on how IT-related lexical units are represented, adapted, and used in English and Uzbek corpus materials. Special attention is paid to frequency, borrowing, semantic adaptation, structural formation, and contextual usage of terms such as computer, software, internet, database, algorithm, platform, and their Uzbek equivalents or borrowed forms. The analysis shows that English IT terms are usually represented as native or internationally standardized technical units, while Uzbek IT terminology demonstrates a strong tendency toward borrowing, transliteration, hybrid formation, and gradual normalization.